Robust Inorganic Hole Transport Materials for Organic and Perovskite Solar Cells: Insights into Materials Electronic Properties and Device Performance. Issue 1 (10th December 2020) - Fakharuddin, Azhar; Vasilopoulou, Maria; Soultati, Anastasia; Haider, Muhammad Irfan; Briscoe, Joe; Fotopoulos, Vasileios; Di Girolamo, Diego; Davazoglou, Dimitris; Chroneos, Alexander; Yusoff, Abd. Rashid bin Mohd; Abate, Antonio; Schmidt-Mende, Lukas; et al.
Abstract : Interfaces in perovskite and organic solar cells play a central role in advancing efficiency and prolong device durability. They improve charge transport/transfer from the absorber layer to the collecting electrodes, while also blocking the opposite charge carriers, minimize voltage losses by suppressing charge recombination. and may act as buffer/protective layers and nanomorphology regulators for the absorber layer. One such interface is formed by the hole transport layer (HTL) and the organic/perovskite absorber. These HTLs typically consist of organic semiconductors, which, although are solution processable at low temperatures and allow perfect energy‐level alignment with the absorber layer and therefore efficient charge collection, are prone to degradation in ambient conditions and under continuous light exposure. In a quest for robust alternatives, inorganic materials such as metal oxides, graphene oxide, bronzes, copper thiocyanate, and transition metal dichalcogenides are actively investigated. However, their hole extraction capability is inferior compared with organic semiconductors as they possess specific energetics leading to significant charge extraction barriers and moderate charge collection. To achieve further advancements in their hole transporting capabilities, strongly interconnecting knowledge of their synthesis, electronic properties, and device performance metrics is required. Abstract : State‐of‐the‐art perovskite and organic solar cells use inorganic hole transport materials (HTMs) due to their superior electronic properties. These HTMs are, however, expensive and prone to degradation. A range of robust inorganic HTMs are emerging, that provide a trade‐off between efficiency, stability, and cost, and are critically reviewed herein.